KONTRIBUSI KOPERASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - perwira, adi; Laila, Yulia (Mu'amalatuna: Jurnal Ekonomi Syariah, 2020)
The purpose of this study is to determine the contribution to economic growth in Indonesia during the past three years. The number of cooperatives decreased by 19%, this decrease was inversely proportional to the increase in the number of members by 23%, total assets increased by 18%, the business volume increased by 13%, and the increase in the number of SHUs generated was 27%. Cooperatives in Indonesia contributed 5.54% to the National Gross Domestic Product. With an asset value of IDR 152.11 trillion and a SHU of IDR 6.26 trillion